Temperature dependent dispersoid stability in ion-irradiated ferritic-martensitic dual-phase oxide-dispersion-strengthened alloy: Coherent interfaces vs. incoherent interfaces. (1st September 2016) - Chen, Tianyi; Gigax, Jonathan G.; Price, Lloyd; Chen, Di; Ukai, S.; Aydogan, Eda; Maloy, S.A.; Garner, F.A.; Shao, Lin
Abstract: In this study, the microstructure of a 12Cr ferritic-martensitic oxide-dispersion-strengthened (ODS) alloy is studied before and after Fe ion irradiation up to 200 peak displacements per atom (dpa). Irradiation temperature ranges from 325 to 625 °C. Before irradiation, both coherent and incoherent dispersoids exist in the matrix. In response to irradiation, the mean sizes of dispersoids in both the ferrite and tempered martensite phases change to equilibrium values that increase with irradiation temperature. The evolution of dispersoids under irradiation is explained by a competition between athermal-radiation-driven shrinkage and thermal-diffusion-driven growth, with interface coherency affecting the growth mechanism. However, each coherency type exhibits different evolution behavior under irradiation. Coherent dispersoids, regardless of their initial size, change toward an equilibrium size at each temperature tested. On the other hand, incoherent dispersoids are destroyed at lower test temperatures but survive while shrinking in size at higher temperatures. This difference in behavior can be explained by the lower interfacial energy of coherent dispersoids in comparison with incoherent dispersoids. This study sheds light on the roles of interface configurations in maintaining dispersoid integrity under irradiation. Graphical abstract: